Дослідження методів вдосконалення детекторів іонізуючого випромінювання на основі мікро- та наноелементів - Вакула, М. Б. (My University, 2022)
The object of study is the interaction of ionizing radiation with the semiconductor material of the ionizing radiation detector based on CdZnTe. The relevance of the work is that it is aimed at increasing the efficiency of detecting ionizing radiation by radiation detectors that are used in many areas of human activity: particle physics, astrophysics, nuclear physics and technology, customs control, medicine, biology, laser physics and optical communication technology. The main types of ionizing radiation detectors, their main characteristics, noise sources in semiconductor detectors and methods of increasing their sensitivity are considered in this work.
Keywords: вдосконалення детекторів; laser physics; іонізуюче випромінювання